COMPRESSIVES IN STUDENT DISCOURSE OF THE INDO-EUROPEAN LANGUAGE ENVIRONMENT - Natalia V. Diachok. (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Philologists are expected to know how to analyze the results of modern nomination processes, especially those that show their belonging to the youth subcode: in word-formation, form-building, other grammatical features of compressives of different representation. Therefore, it is very important to communicate the true meaning of the modern linguistic ideas. The aim of the study is to demonstrate the productivity of compressives as the units of student jargon / discourse, on the one hand, and as the material relevant for its analysis, on the other. To achieve the aim, we have identified the following objectives: 1) to single out compressives among the traditional derivatives; 2) to determine criteria for highlighting the processes of abbreviation and univerbation; 3) to determine the reasons for the emerging of the jargonisms belonging to the type under analysis; 4) to demonstrate the importance of studying compressives in the Indo-European student discourse. Descriptive and structural methods are the main methods of the research as they facilitate the demonstration of the specific aspects of univerb formation and abbreviation as the processes matching the essence of speech compression. The distributive analysis is used to specify the forms of transformation of nominative units. Student discourse is a field of language functioning that produces neologisms resulting from different types of compression. This is connected with the dynamics of student speech as well as the youth’s need to communicate maximum necessary information in the shortest possible time. Obviously, philologists are expected to know how to analyze the results of modern nomination processes, especially those that show their belonging to the youth subcode: in word-formation, form-building, other grammatical features of compressives of different representation. That is why it is so important to communicate the true meaning of these modern linguistic phenomena. The compression phenomena includes the ones that are universal for a whole series of Indo-European languages (e.g. some types of abbreviation), while other phenomena of this type (e.g. univerbation) are not reflected in all languages of this family but observed only in some of them. As a rule, univerbation in its certain morphological manifestations is peculiar to Slavic and Germanic language systems. Abbreviation and univerbation are the main active processes enriching both speech and language with the units under consideration. However, it is reasonable to consider each of those processes by determining the main nominative unit – a nomeme.